Пневмоциліндр двосторонньої дії (Патент на винахід № 117995) - Валіулін, Геннадій Раіфович; Костюк, Володимир Степанович; Кривопляс-Володіна, Людмила Олександрівна; Кушнір, Олена Володимирівна (My University, 2018)
Винахід належить до пневмоприводів, зокрема поворотних пнемоциліндрів, і призначений для реалізації поступального і обертального руху в різноманітних приводах машин і обладнання. The invention relates to pneumatic actuators, in particular rotary pneumatic cylinders, and is intended for the implementation of translational and rotational motion in a variety of drives machines and equipment.
Keywords: пневмопривод; пневмоциліндр; приводи машин; pneumatic actuator; pneumatic cylinder; drives of cars; кафедра мехатроніки та пакувальної техніки